2015
DOI: 10.1002/chp.21290
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CME on Physician Performance and Patient Health Outcomes: An Updated Synthesis of Systematic Reviews

Abstract: Future research on CME effectiveness must take account of the wider social, political, and organizational factors that play a role in physician performance and patient health outcomes. We now have 39 systematic reviews that present an evidence-based approach to designing CME that is more likely to improve physician performance and patient health outcomes. These insights from the scientific study of CME effectiveness should be incorporated in ongoing efforts to reform systems of CME and health care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
307
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(338 citation statements)
references
References 30 publications
11
307
0
4
Order By: Relevance
“…Cervero and Gaines [1] have convinced most sceptics that medical performance and patient outcomes are improved by CME, if it is structured appropriately. We know that needs assessment is essential, multi-media is preferable to single media, case- and workplace-based education is better that didactic lectures, repetition is important and, crucially, the education must be active rather than passive.…”
mentioning
confidence: 99%
“…Cervero and Gaines [1] have convinced most sceptics that medical performance and patient outcomes are improved by CME, if it is structured appropriately. We know that needs assessment is essential, multi-media is preferable to single media, case- and workplace-based education is better that didactic lectures, repetition is important and, crucially, the education must be active rather than passive.…”
mentioning
confidence: 99%
“…This helps education planners recognise where to begin planning learning activities for physicians (a gap analysis should be completed at each outcome level starting with level 7 until no gap is detected). When it comes to the impact of CME on performance and on patient health outcomes, Cervero and Gaines remind us that one of the four primary influences of improved outcomes was that CME is based on practice-based needs assessment [8]. In summary, a deeper insight into practice and practice needs and gaps within a specialty area should be of great benefit for an educational organisation.…”
Section: Discussionmentioning
confidence: 99%
“…8 These reviews have consistently demonstrated that CME more reliably impacts provider knowledge and performance versus patient outcomes. 8 Further, traditional CE activities (conferences, symposia, lectures) improve participant knowledge but generally have a very limited effect on improving clinician practice and patient outcomes. 8 Examples of published practice improvements include screening practices, prescribing, and adhering to guideline measurements.…”
Section: Introductionmentioning
confidence: 99%
“…8 Further, traditional CE activities (conferences, symposia, lectures) improve participant knowledge but generally have a very limited effect on improving clinician practice and patient outcomes. 8 Examples of published practice improvements include screening practices, prescribing, and adhering to guideline measurements. Patient outcome measurements include a broad array of clinical endpoints such as smoking cessation, diet, or blood pressure in patients with hypertension, to name a few.…”
Section: Introductionmentioning
confidence: 99%